Determination of uranium and thorium in water for human consumption in the county of Angra dos Reis - Mariana Ferreira Gonçalves; Ana Cristina de Melo Ferreira; Amanda Balassiano Carvalhal (Brazilian Journal of Radiation Sciences, 2021)
Studies indicate that the presence of uranium and thorium radionuclides in the environment are of great importance in monitoring radiation levels. Humans can have a direct or indirect exposure. The radiological impact for the members of the population living in Angra dos Reis - RJ was evaluated using environmental monitoring data of uranium and thorium in the waters for human consumption of the county of Angra dos Reis. Monitoring data showed concentrations much lower than the guidelines based on the maximum permitted value of uranium in waters for consumption established by CONAMA. Thorium is the most significant radionuclide. The public that lives in the county of Angra dos Reis is not exposed to the radiation that would result in a radiological impact.